Inovasi Evaluasi Pembelajaran Elemen Seni Lukis Berbasis Crossword - RIZKYHIMAWAN, ADHYTIA; Wahyu Lestari; Udi Utomo (Jurnal Senirupa Warna, 2025)
This study aims to explore the potential for innovation in the evaluation of learning elements of painting based on crosswords in the context of education, learning painting has an important role in developing students' abilities to observe, imagine, and communicate through visual mediums. However, traditional evaluation is often limited to written tests or practical projects that may pay less attention to aspects of students' creativity and imagination. Therefore, innovation is needed in the evaluation of learning elements of painting. One interesting approach is to use game elements in the evaluation process, such as crosswords. This study uses research and development methods referring to Sugiyono and data collection techniques through observation, interviews, and documentation. Data were analyzed using an interactive method explained by Prof. Tjetjep Rohendi Rohidi. It is hoped that by introducing painting crosswords as a medium in learning, students can be more involved in the process of learning painting, increase their understanding of important concepts, and develop critical thinking skills and creativity. Suggestions for teachers are to utilize this evaluation tool in other subjects, with the implications of using technology in independent curriculum-based learning.